Bottom‐up processes in a declining yellow‐footed rock‐wallaby (Petrogale xanthopus celeris) population. (8th October 2014) - Sharp, Andy; McCallum, Hamish
Abstract: Populations of large herbivores are generally considered to be food limited, escaping the regulatory effects of predation through their large body size, migratory behaviour and/or the occurrence of alternate prey species. In the Australian arid and semi‐arid zones, the availability of forage biomass is considered to be the primary driver of fluctuations in kangaroo abundance. However, little is known about the population dynamics of the smaller sympatric macropods. We examined the demographic traits of a large colony of yellow‐footed rock‐wallabies ( P etrogale xanthopus celeris ), following a 2‐year period of above average rainfall. The population was located within a conservation reserve that was subject to a predator control program around its perimeter and on neighbouring properties. The low predator abundance provided an opportunity to gauge the strength of bottom‐up population processes. During the two years of the study, the population declined in size by 53%, resulting from both the virtual absence of juvenile recruitment and the loss of adult wallabies. Although reproductive output was high, low pouch young and juvenile survival rates resulted in few individuals progressing into the adult population. With minimal recruitment, the rate of population decline ( r  = 0.77) matched the observed adult survival rate (Φ = 0.76). Despite average rainfall conditions during the study, survival rates across all age‐classes were equivalent to those reported for other rock‐wallaby populations during periods of scarcity. The reduced survival rates were attributed to low levels of forage resources, particularly around the wallabies' refuge sites, suggesting the bottom‐up regulation of the colony at high densities. The data suggest that the colony was at temporarily high abundance, following a rainfall driven pulse of recruitment. Conservation management actions for this species should focus on increasing juvenile survival rates within declining populations, through the control of feral goats ( C apra hircus ), rabbits ( O ryctolagus cuniculus ) and red foxes ( V ulpes vulpes ).